In Nehemiah's Footsteps? Uzziah at the Service of the Chronicler's Ideology - Gluska, Eran; Lipschits, Oded (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2023)
Uzziah ruled in Judah for many years, yet the description of his rule in the book of Kings is laconic. The book of Chronicles, on the other hand, provides an extensive description of his reign that stems from authorial ideology, theology, and processes of identity formation. The book of Ezra-Nehemiah describes a series of confrontations from four directions, with Uzziah’s battles with the Philistines, the Arab tribes, and the Ammonites being three of these fronts. The Chronicler, writing several decades after Ezra-Nehemiah, was aware of the Ezra-Nehemiah text or its narrative, and developed the figure of Uzziah as a great king, thus serving his own national, economic, ethnic, and religious goals.